Information System of Diploma Companion Certificate in South Aceh Polytechnic - Arinal Ihsan; Nurul Safitriana; Sepri Kurniadi (LPPM Politeknik Aceh Selatan, 2024)
As an institution providing higher vocational education, the South Aceh Polytechnic (POLTAS) must of course be consistent in carrying out innovations and policies regarding the development of information technology in improving services for the use of systems implemented within the campus. South Aceh Polytechnic issued a policy in 2023 regarding the issuance of Diploma Companion Certificates. The problem formulation in this research is how to build, design and collect the results of an information system that is able to adapt dynamically in assessing student activities while they are active students at the South Aceh Polytechnic, which is realized in a certificate accompanying the diploma. The aim of this research is to build a South Aceh Polytechnic Diploma Companion Certificate Information System (SISKPI), which provides information about a graduate's field of expertise to agencies or industry to obtain professional workers. This type of research is applied research with a case study at the South Aceh Polytechnic